2017
DOI: 10.7146/hjlcb.v26i51.97439
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and Qualitative Aspects of Advanced Learners’ L1 and L2 Mastery of Polysemous Words

Abstract: In the present investigation, 15 fi rst-term university students were faced with forty decontextualised polysemous words in English (L2) and Swedish (L1) respectively and asked to indicate which, of a set of six meanings, adhered to the item in question (two to fi ve of the meanings were correct). The polysemous words were of varying frequency. The investigation thus addresses the following research question:In quantitative and qualitative terms, what knowledge do advanced students have of polysemous words in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…The last finding is consistent with what Karlsson found in his study in 2013 that students have a better command of the most frequent meaning of polysemous words than the less frequent ones [8]. And also Zhang and Wen have found that Chinese students tend to know more about the highfrequency senses of English polysemous phrasal verbs than the low-frequency ones [15].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The last finding is consistent with what Karlsson found in his study in 2013 that students have a better command of the most frequent meaning of polysemous words than the less frequent ones [8]. And also Zhang and Wen have found that Chinese students tend to know more about the highfrequency senses of English polysemous phrasal verbs than the low-frequency ones [15].…”
Section: Discussionsupporting
confidence: 89%
“…Sometimes the core meaning is followed by semantically closest meanings, with more marginal uses appearing later [7]. Karlsson found that Swedish advanced speakers of L2 could get only a third of the full score on average on a multiple-choice test covering forty polysemous words, appearing to know the most frequent sense of a polysemous word better than the less frequent ones [8].…”
Section: Factors Affecting Students' Acquisition Of Polysemous Wordsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because it is a widely encountered phenomenon and the number of senses is particularly high in high-frequency words, polysemy causes problems to foreign language learners at all levels. The studies (Schmitt, 1998, Karlsson, 2013Öztürk, 2018) show that even advanced learner's knowledge of different senses is inadequate. This inadequacy leads to problems in foreign language teaching both in terms of language production and comprehension (Watanabe, 2014;Saito, Webb & Trofimovich, 2016;Öztürk, 2017).…”
Section: Introductionmentioning
confidence: 99%